Juror in the Category Branding design, Typography, Package Design, Publishing Design - Mouzouropoulos, Theseas (My University, 2026)
A distinguished jury, composed of both educators and industry professionals, conducts the judging process for the ADCE Student Awards. They select one Gold winner in each category, as well as the standout “Youngestar” – the overall jury for the 2025 edition has now been oﬃcially announced, featuring over 50 experts, including professionals and tutors, with more names coming soon. Judging begun online on September 15th, with the winners revealed during ADCE Creative Week at the first-ever Awards Gala dedicated exclusively to the student competition.